QUANTIFICATION OF THE ECONOMIC EFFECT FROM THE MANAGEMENT OF STATE FINANCE OF UKRAINE - KHOMUTENKO, Alla (Scientific journal «World of Finance», 2021)
Introduction. The results achieved in managing state finances can be expressed through organizational, social and economic effects. They are dialectically related and, to a large extent, determine the degree of satisfaction of public interests that change over time. Financial indicators obtained in the budget sphere and in the state sector of the economy, characterize the economic effect of managing state finances. Economic effect, as a rule, confirms the feasibility of a functioning managerial apparatus and the effectiveness of its decisions in all spheres of society.The purpose of the article is to evaluate the economic effect of managing state finances of Ukraine, based on the author’s methodological approach, and substantiate the directions for its increase.Results. The indicators of the economic effect of state finance management are defined in the article. The analysis of individual indicators of fiscal, debt, investment and innovation stability in the state, as well as the financial stability of subjects of the state sector of the economy for 2008–2018. The tendencies of performance indicators of the plan of the State Budget of Ukraine, the reliability of the profitable part of Pension Fund of Ukraine, revenues from privatization, external state debt, efficiency and level of mastering of budget investments are established. The number and structure of the state sector, its financial contribution to the national economy are investigated. The necessity of carrying out a number of priority measures that will positively affect the indicators of the economic effect of managing state finances of Ukraine is substantiated.Conclusions. According to the results of the assessment of the economic effect of the efficiency of state finance management it is necessary to apply measures aimed at ensuring budgetary, debt, investment and innovation stability and financial stability of state sector entities. For example, it is necessary to improving the management of state-owned enterprises, in particular: 1) to change methodological approaches to assessing the effectiveness of state sector management; 2) to establish the relationship between the budget funding of the state sector of the economy and the results of its work; 3) to use budget lending as a tool for managing the initial financial flows of the state budget; 4) to increase the responsibility of heads of state enterprises for the results achieved by them. It is proposed to improve the management of budget investments due to: 1) the development of the institution of public-private partnership in certain areas of the economy such as infrastructure, science, etc.; 2) intensification of the use of innovation potential through the creation of innovation clusters, business incubators, etc.; 3) improving the quality of evaluation of the investment project, which will positively affect the effectiveness of its implementation; 4) reorientation of the directions of movement of funds from investments in means of production to investments in human resources, which has a long-term perspective, but with higher profitability; 5) securing for the state intellectual property rights for the development of state research institutes (patents, certificates, etc.), which will provide additional revenue from franchises and trademarks.